2020
DOI: 10.1007/s00066-020-01712-x
|View full text |Cite
|
Sign up to set email alerts
|

Radiation oncology as part of medical education—current status and possible digital future prospects

Abstract: Purpose Education as part of medical education is currently changing rapidly. Not least because of the corona crisis, more and more digital teaching formats and innovative teaching concepts such as the flipped classroom model are finding their way into teaching. We analyzed the acceptance and effectiveness of traditional teaching methods as well as the interest in innovative e‑learning methods among medical students in the field of radiation oncology at the medical school of the Technical University of Munich.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Additionally, datasets showed no significant differences in coping behavior, self-efficacy or emotional status Collado-Valero et al, ( 2021 ) Spain teachers Education science Comparative research quantitative 45 The results revealed an increase in the implementation of FC during the pandemic. Teachers considered that the circumstances encouraged the implementation of FC Dapper et al, ( 2020 ) Germany students Medical education (radiation oncology) graduate Case-study research mixed 125 Traditional teaching methods were largely accepted by students, but opinions on the application of alternative teaching methods or e-learning formats, in particular on the application of FC method, differed widely Durfee et al, ( 2020 ) USA students Medical education (radiology) graduate Action research mixed 111 Virtual radiology core clerkship design included online FC modules and this was shown to be successful, since student performance on the standardized final exam was similar to the in-person teaching Feijóo et al, ( 2021 ) Spain, Peru students Engineering undergraduate Action research mixed 220 Authors concluded that the flipped teaching methods implemented by them during the pandemic shift to remote teaching suffered less than other classical teaching approaches, not only with regards to lectures but also to the outcomes Hoshang et al, ( 2021 ) UAE students and teachers Information systems and Engineering undergraduate Action research mixed 300 students and 10 teachers Students and teachers were in favor of FC usage, but not strongly and without criticism. More training in the tools and concepts of FC is required.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, datasets showed no significant differences in coping behavior, self-efficacy or emotional status Collado-Valero et al, ( 2021 ) Spain teachers Education science Comparative research quantitative 45 The results revealed an increase in the implementation of FC during the pandemic. Teachers considered that the circumstances encouraged the implementation of FC Dapper et al, ( 2020 ) Germany students Medical education (radiation oncology) graduate Case-study research mixed 125 Traditional teaching methods were largely accepted by students, but opinions on the application of alternative teaching methods or e-learning formats, in particular on the application of FC method, differed widely Durfee et al, ( 2020 ) USA students Medical education (radiology) graduate Action research mixed 111 Virtual radiology core clerkship design included online FC modules and this was shown to be successful, since student performance on the standardized final exam was similar to the in-person teaching Feijóo et al, ( 2021 ) Spain, Peru students Engineering undergraduate Action research mixed 220 Authors concluded that the flipped teaching methods implemented by them during the pandemic shift to remote teaching suffered less than other classical teaching approaches, not only with regards to lectures but also to the outcomes Hoshang et al, ( 2021 ) UAE students and teachers Information systems and Engineering undergraduate Action research mixed 300 students and 10 teachers Students and teachers were in favor of FC usage, but not strongly and without criticism. More training in the tools and concepts of FC is required.…”
Section: Resultsmentioning
confidence: 99%
“…As expected, many difficulties were encountered at the beginning of online teaching during COVID-19. In several studies students reported to be dissatisfied with online learning in general, and especially with communication with teachers (Tang et al, 2020 ; Dapper et al, 2020 ). Furthermore, teachers noticed problems with student engagement in online learning.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the mostly provisional offerings during the COVID pandemic, these formats will gain importance in future curricula. In the future, hybrid courses consisting of virtual and face-to-face courses, self-study, lecture, seminar, patient teaching, and case discussion will be interlinked [ 17 , 18 ]. In principle, very complex hybrid formats lend themselves to the teaching of radiation oncology due to its highly interdisciplinary nature and the linking of basic and clinical knowledge as well as competency-based skills [ 19 ].…”
Section: At Which Point and In Which Teaching Format Can These Topics Be Anchored In The New Curriculum?mentioning
confidence: 99%